"Dig where you stand" : proceedings of the conference "On-going research in History of Mathematics Education" June 20-24, 2009, at Fjölbrautaskólinn í Garðabæ, Garðabær, Iceland - Kristín Bjarnadóttir 1943- (2009)
Editors: Kristín Bjarnadóttir, Fulvia Furinghetti, Gert Schubring On-going research in the History of Mathemtics Education (2009 : Garðabær) John Playfair in the natural philosophy classroom / Amy Ackerberg-Hastings -- . -- The evolution of the journal L'Enseignement Mathématique from its initial aims to new trends / Fulvia Furinghetti -- The Italian contribution to the International Commission on Mathematical Instruction from its founding to the 1950s / Livia Giacardi -- From descriptive history ot interpretation and explanation : a wave modes for the development of mathematics education in Denmark / Hans Christian Hansen -- ICMI in the post-Freudenthal era : moments in the history of mathematics education from an international perspective / Bernard R. Hodgson -- Toward a cognitive historiography of mathematics education / Iason Kastanis and Nikos Kastanis -- The social efficiency movement in the United States and its effects on School mathematics / Jeremy Kilpatrick -- Changing representations and practices in school mathematics : the case of Modern Math in Portugal / José Manuel Matos -- The teaching of intuitive geometry in early 1900s Italian Middle School : programs, mathematicians' views and praxis -- Professional debate and social structure in Swedish mathematics education, 1905-1962 : the case of geometry instruction at the lower secondary level / Johan Prytz -- Teaching new geometrical methods with an ancient figure in the nineteenth and twentieth centuries : the new triangle geometry in textbooks in Europe and USA (1888-1952) / Pauline Romera-Lebret -- How to relate regional history to general patterns of history? : the case of mathematics / Gert Schubring -- Mathematics education in East Asia from antiquity to modern times / Man Keung Siu -- Foreign influences on Dutch mathematics teaching / Harm Jan Smid -- History of mathematics education in training teachers of mathematics : considering its potentialities / Wagner Rodrigues Valente -- .